Effect of Chinese Herbal Medicine Therapy on Overall and Cancer Related Mortality in Patients With Advanced Nasopharyngeal Carcinoma in Taiwan - Wang, Chen-Yu; Wang, Tang-Chuan; Liang, Wen-Miin; Hung, Chien-Hui; Chiou, Jian-Shiun; Chen, Chao-Jung; Tsai, Fuu-Jen; Huang, Sheng-Teng; Chang, Ta-Yuan; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; et al. (Frontiers in Pharmacology, 2021)
Nasopharyngeal carcinoma (NPC) is a head and neck cancer involving epithelial squamous-cell carcinoma of the nasopharynx that mainly occurs in individuals from East and Southeast Asia. We investigated whether Chinese herbal medicine (CHM) as a complementary therapy offers benefits to these patients. We retrospectively evaluated the Taiwan Cancer Registry (Long Form) database for patients with advanced NPC, using or not using CHM, between 2007–2013. Cox proportional-hazard model and Kaplan‒Meier survival analyses were applied for patient survival. CHM-users showed a lower overall and cancer-related mortality risk than non-users. For advanced NPC patients, the overall mortality risk was 0.799-fold for CHM-users, after controlling for age, gender, and Charlson comorbidity index (CCI) score (Cancer stages 3 + 4: adjusted hazard ratio [aHR]: 0.799, 95% confidence interval [CI]: 0.676–0.943, p = 0.008). CHM-users also showed a lower cancer-related mortality risk than non-users (aHR: 0.71, 95% CI: 0.53–0.96, p = 0.0273). Association rule analysis showed that CHM pairs were Ban-Zhi-Lian (BZL; Scutellaria barbata D.Don) and For single herbs, Bai-Hua-She-She-Cao (Herba Hedyotis Diffusae; Scleromitrion diffusum (Willd.) R.J.Wang (syn. Hedyotis diffusa Willd.) and Mai-Men-Dong (MMD; Ophiopogon japonicus (Thunb.) Ker Gawl.), and Gan-Lu-Yin (GLY) and BHSSC. Network analysis revealed that BHSSC was the core CHM, and BZL, GLY, and Xin-Yi-Qing-Fei-Tang (XYQFT) were important CHMs in cluster 1. In cluster 2, ShengDH, MMD, Xuan-Shen (XS; Scrophularia ningpoensis Hensl.), and Gua-Lou-Gen (GLG; Trichosanthes kirilowii Maxim.) were important CHMs. Thus, as a complementary therapy, CHM, and particularly the 8 CHMs identified, are important for the treatment of advanced NPC patients.